2013
DOI: 10.1111/ecc.12124
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral antineoplastic agents by cancer patients: definition and literature review

Abstract: Since the 1990s, oral chemotherapy has been gaining ground as cancer treatment. This therapy seems to have few toxic effects and offers patients good quality of life. However, in addition to the fears the therapy might generate in patients, oral treatment raises a new issue, which, until now, has been marginal in this field: therapeutic observance or adherence. We investigated the research into adherence to oral chemotherapy among cancer patients published between 1990 and July 2013. Studies showed considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 61 publications
(146 reference statements)
2
64
1
1
Order By: Relevance
“…Although several reviews of adherence to oral antineoplastic therapies have been published [8,12,69,70], only a few were based on the systematic reporting criteria per PRISMA guidelines [10,11,68]. Furthermore, we examined observational, retrospective database, cohort, and randomized intervention studies to describe not only rates and correlates of adherence but also empirical efforts to date to improve proper administration of these oral agents.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Although several reviews of adherence to oral antineoplastic therapies have been published [8,12,69,70], only a few were based on the systematic reporting criteria per PRISMA guidelines [10,11,68]. Furthermore, we examined observational, retrospective database, cohort, and randomized intervention studies to describe not only rates and correlates of adherence but also empirical efforts to date to improve proper administration of these oral agents.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Most studies have included heterogeneous target tumor types, regimens, and therapy settings [16]. Adherence with capecitabine is relatively high compared with other oral cancer chemotherapies [17,18]. Some studies have suggested that only one specific group of patients are nonadherent and that adherence-enhancing interventions should be targeted at this group alone [17,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this study is that it targets a challenging clinical problem among patients with a life-threatening disease, assisting patients to lower symptom severity, improve adherence, and continue their cancer treatment (Bassan et al 2014, Puts et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients are known to experience symptoms from side effects of treatment and miss as much as one-third of the prescribed OA doses required for treatment of the cancer (Spoelstra et al 2013, Bassan et al 2014, Puts et al 2014. Thus, a need exists to test interventions to train patients to self-manage when OAs are prescribed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation